Expression and in vitro properties of guinea pig IL-5: Comparison to human and murine orthologs. Issue 3 (2000) - Scott, Clay W; Budzilowicz, Carol; Hubbs, Stephen J.; Stein, Mark; Sobotka-Briner, Cindy; Wilkins, Deidre E.
Abstract : Interleukin-5 (IL-5) is a key mediator of eosinophilic inflammation. The biological role of this cytokine in an allergic airway inflammatory response has been widely demonstrated in guinea pigs, yet the interaction of guinea pig IL-5 (gpIL-5) with its receptor has not been studied. Experiments were performed to quantitate the interaction of gpIL-5 with gpIL-5r and to compare this affinity with that of hIL-5 and mIL-5 and their cognate receptors. The cross-species affinity and agonist efficacy were evaluated to see if gpIL-5r had a restricted species reactivity (as is the case with mIL-5r) or did not distinguish between IL-5 orthologs (similar to hIL-5r). gpIL-5 was cloned using mRNA isolated from cells obtained by bronchoalveolar lavage. Recombinant gpIL-5 was expressed in T.ni insect cells and purified from spent media. Binding assays were performed using insect cells expressing hIL-5rαβ or gpIL-5rαβ1 as previously described ( Cytokine, 12:858–866, 2000) or using B13 cells which express mIL-5r. The agonist potency and efficacy properties of each IL-5 ortholog were evaluated by quantitating the proliferative response of hum an TF-1 cells and murine B13 cells. gpIL-5 bound with high affinity to recombinant gpIL-5r as demonstrated by displacing [ 125 I]hIL-5 ( K i = 160 pM). gpIL-5 also bound to hIL-5r with high affinity ( K i = 750 pM). hIL-5 and mIL-5 showed similar, high-affinity binding profiles to both gpIL-5r and hIL-5r. In contrast, gpIL-5 and hIL5 did not bind to the mIL-5r as demonstrated by an inability to displace [ 125 I]mIL-5, even at 1000-fold molar excess. These differences in affinity for IL-5r orthologs correlated with bioassay results: human TF1 cells showed roughly com parable proliferative responses to guinea pig, hum an and murine IL-5 whereas murine B13 cells showed a strong preference for murine over guinea pig and human IL-5(EC50 = 1.9, 2200 and 720 pM, respectively). Recombinant gpIL-5 binds to the gpIL-5r with high affinity, similar to that seen with the human ligand-receptor pair. gpIL-5r and hIL-5r do not distinguish between the three IL-5 orthologs whereas mIL-5r has restricted specificity for its cognate ligand.